Gap disturbance regime and composition in the Atlantic Montane Rain Forest: the influence of topography - Ferreira de Lima, Renato Augusto [UNESP]; de Moura, Leila Cunha [UNESP] (Springer, 2008)
In the Atlantic Montane Rain Forest of south-eastern Brazil, a field study was carried out to describe the forest disturbance regime, analyse canopy gap composition and evaluate the influence of habitat parameters on gap tree species composition. We characterized canopy gaps considering the group of variables as follows: area, type and number of tree/branch falls, topographic position, soil coverage and surrounding canopy trees. Gap composition was assessed at species level by measuring all individuals inside gaps higher than one meter. Mean gap area of the 42 canopy gaps analysed was 71.9 +/- 9.0 m(2) (mean +/- SE). Out of the studied gaps, 35.7% were created by uprooted and by snapped trees, 16.7% by dead-standing trees and 11.9% by the fall of large branches. The disturbance regime was characterized by gap openings predominantly smaller than 150 m(2) and by spatial patterning related to topography. Ridges had smaller gaps and higher proportions of gaps created by branch falls; slopes had bigger gaps generally created by uprooting events. The more abundant and frequent species were shade tolerant and the more species-rich families found inside gaps did not differ from the forest as a whole. Pioneer species were rare and restricted to medium and large size classes. The Indicator Species Analysis and the Canonical Correspondence Analysis indicated gap area, topography and the percentage of soil cover by the genera Calathea and Ctenanthe were the predominant variables correlated with woody species distribution. So, topography emerged as an important issue not only to the gap disturbance regime, but also to gap colonization. In respect to the influence of gap processes on the Atlantic Montane Rain Forest regeneration, our results support the view that canopy gap events may not be working as promoters of community wide floristic shifts.
Keywords: canopy gaps; gap composition; south-eastern Brazil; treefalls; Tropical Montane Rain Forest